Diagnostic accuracy of early magnetic resonance imaging to determine motor outcomes in infants born preterm: a systematic review and meta‐analysis. (29th November 2017) - George, Joanne M; Pannek, Kerstin; Rose, Stephen E; Ware, Robert S; Colditz, Paul B; Boyd, Roslyn N
Abstract : Aim: To examine the diagnostic ability of early magnetic resonance imaging (MRI; <36wks postmenstrual age) to detect later adverse motor outcomes or cerebral palsy (CP) in infants born preterm. Method: Studies of infants born preterm with MRI earlier than 36 weeks postmenstrual age and quantitative motor data or a diagnosis of CP at or beyond 1 year corrected age were identified. Study details were extracted and meta‐analyses performed where possible. Quality of included studies was evaluated with the QUADAS‐2 (a revised tool for the quality assessment of diagnostic accuracy studies). Results: Thirty‐one articles met the inclusion criteria, five of which reported diagnostic accuracy and five reported data sufficient for calculation of diagnostic accuracy. Early structural MRI global scores detected a later diagnosis of CP with a pooled sensitivity of 100% (95% confidence interval [CI] 86–100) and a specificity of 93% (95% CI 59–100). Global structural MRI scores determined adverse motor outcomes with a pooled sensitivity of 89% (95% CI 44–100) and a specificity of 98% (95% CI 90–100). White matter scores determined adverse motor outcomes with a pooled sensitivity of 33% (95% CI 20–48) and a specificity of 83% (95% CI 78–88). Interpretation: Early structural MRI has reasonable sensitivity and specificity to determine adverse motor outcomes and CP in infants born preterm. Greater reporting of diagnostic accuracy in studies examining relationships with motor outcomes and CP is required to facilitate clinical utility of early MRI. What this paper adds: Early magnetic resonance imaging (MRI) has reasonable sensitivity and specificity to determine later adverse motor outcomes and cerebral palsy (CP). Detection of infants who progressed to CP was stronger than motor outcomes. Global MRI scores determined adverse motor outcomes more accurately than white matter scores. Few studies report diagnostic accuracy of early MRI findings. Diagnostic accuracy is required to draw clinically meaningful conclusions from early MRI studies. What this paper adds: Early magnetic resonance imaging (MRI) has reasonable sensitivity and specificity to determine later adverse motor outcomes and cerebral palsy (CP). Detection of infants who progressed to CP was stronger than motor outcomes. Global MRI scores determined adverse motor outcomes more accurately than white matter scores. Few studies report diagnostic accuracy of early MRI findings. Diagnostic accuracy is required to draw clinically meaningful conclusions from early MRI studies. This article is commented on by Arulkumaran and Arichi on page116 of this issue. This article's abstract has been translated into Spanish and Portuguese. Follow the links from theabstract to view the translations.